Fuzzy MCDM methods application in radio resource management for modern communication systems - M. Alkhawlani, Mohammed (International Journal of Engineering and Technology, 2019)
Fuzzy MCDM methods are a hybrid multi criteria decision making systems where the advantages for both fuzzy logic theory and the traditional MCDM are utilized. Fuzzy MCDM systems take into account the insufficient information and the evolution of available knowledge and they are very useful to deal with the uncertain and imprecise data. The radio resource management mechanisms in modern communication systems are typical multi criteria problems and the usage of MCDM systems is mandatory to reduce the influence of the imprecise, contradictory, and dissimilar measurements of these complex communication systems. In this paper, two different fuzzy MCDM systems are developed to address one of the most important radio resources management mechanisms which is vertical handover (VHO). These systems use fuzzy AHP and fuzzy SAW methods. Illustrative numerical examples for the developed systems are presented. The examples show that the choice of the MCDM tool can directly affect the ranking order of the available access networks, and hence, the selection of the MCDM methods is highly critical in any VHO solution. Â Â